PERLINDUNGAN HUKUM PEMILIK MEREK TERDAFTAR DAN RELEVANSINYA TERHADAP PRAKTEK PERSAINGAN USAHA TIDAK SEHAT - Hendra Pratama, Putu; Supasti Dharmawan, Ni Ketut; Sukihana, Ida Ayu (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
Brand is an economic asset for its owners, both individuals and companies (legal entities) that can generate huge profits, of course, when utilized with respect to aspects of business and management processes are good, because the Right to Use Trademark often related to monopolistic practices and unfair business competition healthy then attached to her legal protection, as objects related to them the rights of individuals or legal entities. Important legal protection of intellectual property rights is a registered Trademark particularly against unfair competition. This study aims to determine the relevance of a trademark registration pertaining to the existence of unfair business practices by applicable Indonesian laws and legal effect of brand owners who have not registered. The data used in this study is a secondary data obtained from the literature, from the Law and literature books of jurisprudence and other legal writings relevant to the issues. This type of research is to solve the problems of normative legal research. In discussing the issues contained in this research used the qualitative method then the data is presented in descriptive and systematic. So that it can be seen besides getting legal protection registered brand owners will also get exemption from unfair business practices, especially in the case of monopoly goods and services. So brand owners who have not registered will not get any protection or exclusion of the practice of business competition.
Keywords: Protection Law, Trademark Registration, unfair competition